Simulation of a surface transverse wave biosensor for DF-1 cells - Jamil, Nadira; Nordin, Anis Nurashikin; Mel, Maizirwan; Voiculescu, Ioana (2010)
A 250MHz Surface-Transverse Wave (STW) resonator is employed as a sensor element for the detection of DF-1 cells. STWs are horizontally polarized shear waves which are generated and detected by the interdigitated transducers (IDTs) similar to surface-acoustic wave (SAW) resonators. Detection of chemical and biological agents in aqueous solutions is a difficult problem, especially when the detection technique has to be sensitive, power-efficient and very handy. This paper presents the biosensor prototype utilizing STW resonator. The two-dimensional finite element (FEM) modeling of the STW resonator was performed using COMSOL Multiphysics #x2122;. 200MHz operating frequency was applied in the simulation. The FEM simulations results are equal with the theoretical results where an operating frequency of 200MHz will produce a resonance frequency of 200MHz.